Campylobacter jejuni and Campylobacter coli serotypes isolated from chickens, cattle, and pigs. - Munroe, D L (1983)
A total of 191 Campylobacter jejuni and 125 Campylobacter coli were isolated from the intestinal content of 398 chickens, 421 cattle, and 203 pigs. All 108 chicken isolates and 73 of 80 cattle isolates were C. jejuni, but 115 of the 118 pig isolates were C. coli. A total of 84% of the C. jejuni and 64% of the C. coli isolates were typed on the basis of thermostable antigens with 20 antisera prepared against frequently occurring serotypes in Campylobacter enteritis in man (15 C. jejuni, 6 C. coli serotypes). A total of 96% of the chicken isolates and 67% of the cattle isolates belonged to 11 C. jejuni serotypes that occur most frequently in human cases of enteritis (serotypes 1, 2, 3, 4, 5, 13/16, 18, 21, 23, 31, and 36). Serotype 8, a relatively common human isolate, was not recovered. The C. coli isolates from pigs belonged to serotypes uncommon among human isolates.